High-toughness tunnel filling material
By using aminated modified short-cut ellowite nanotubes, toughening component B and iron-doped nanozinc oxide component C, a high-toughness tunnel filling material was prepared, which solved the problem of low bending strength and easy cracking in tunnel filling of existing cement mortar, and achieved high toughness and fatigue resistance of the material.
Patent Information
- Application Number
- CN202510091137.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-20
- Publication Date
- 2025-04-25
AI Technical Summary
The existing cement mortar lacks deformation recovery ability, low bending strength, and easy cracking in tunnel filling, making it difficult to meet the requirements of tunnel engineering tensile and bending strength.
A high-toughness tunnel filling material including amidated modified chopped elolite nanotubes (component A), component B with excellent toughening performance and component C containing iron doped nanozinc oxide was prepared by chemical curing reaction at room temperature.
The prepared material has high toughness, fatigue resistance and isotropy, and can be cured and molded at room temperature, significantly improving the overall mechanical properties of the tunnel filling material.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tunnel engineering material preparation, and in particular to a high-toughness tunnel filling material. Background Art
[0002] In the field of underground engineering, cement mortar is generally used to fill the cavity of the outer wall of the tunnel. The defects of cement mortar, such as lack of deformation recovery ability, low bending strength, and easy cracking with temperature changes, are serious hidden dangers to the overall life and safety of the tunnel. With the improvement of safety requirements for tunnel engineering design, the toughness of conventional cement mortar can no longer meet the tensile and bending strength required by the project. In order to cope with the complex and harsh stress environment of the outer wall of the tunnel, the development of a filling material with high toughness is an engineering problem that needs to be solved urgently. Summary of the invention
[0003] In view of the above problems, the present invention provides a high-toughness tunnel filling material.
[0004] The purpose of the present invention is achieved by the following technical solutions:
[0005] A high-toughness tunnel filling material comprises component A, component B and component C, wherein the preparation method of component A comprises the following steps:
[0006] A1. Disperse short-cut halloysite nanotubes in water, adjust the pH to alkaline, add sodium hexametaphosphate, stir and mix, and then perform ultrasonic treatment. Centrifuge the mixed system after ultrasonication at 1000-2000 rpm for 10-20 min, take the supernatant and centrifuge at 3000-4000 rpm for 15-25 min, take the supernatant and centrifuge at 6000-7000 rpm for 20-30 min, take the supernatant and centrifuge at 9000-10000 rpm for 25-35 min, collect the precipitate and set aside;
[0007] A2, ultrasonically dispersing the short-cut halloysite nanotubes obtained in step A1 in an alkaline Tween 20 aqueous solution, separating the precipitate, washing with water, drying, mixing with γ-aminopropyltriethoxysilane and anhydrous sodium carbonate, stirring and reacting at 80-85° C. for 22-28 hours, cooling after the reaction, separating the precipitate and washing with anhydrous ethanol and tetrahydrofuran, respectively, vacuum drying, adding to polytetrahydrofuran ether glycol, and ultrasonically dispersing and mixing to obtain the component A;
[0008] The preparation method of component B comprises the following steps:
[0009] B1, adding guanidine carbonate and ethyl acetoacetate to anhydrous ethanol, stirring and reacting at 78-80° C. for 12-18 hours, cooling to room temperature, separating the precipitate and washing with deionized water, ethanol and acetone, and drying to obtain product 1;
[0010] B2, adding the product 1 to hexamethylene diisocyanate, stirring and reacting at 98-100° C. for 16-20 hours, cooling to room temperature, adding petroleum ether, stirring and mixing, separating the precipitate, washing with petroleum ether, and drying to obtain product 2;
[0011] B3, adding the product II and 2-amino-1,3-propanediol to N,N-dimethylformamide, stirring and reacting at 98-100° C. for 4-7 hours, removing the precipitate, adding a mixed solution of ethyl acetate and petroleum ether to the supernatant, stirring and mixing thoroughly, separating the precipitate and washing it with anhydrous acetone, and drying to obtain the product III;
[0012] B4, adding the product three to the polymer polyol, and mixing thoroughly to obtain the component B;
[0013] The preparation method of component C comprises the following steps:
[0014] C1. Mix anhydrous sodium bicarbonate and zinc sulfate heptahydrate and perform ball milling. Wash the ball milled product with deionized water, heat it to 200-250° C. and keep it for 3-5 hours, and then cool it to obtain product 4. Mix product 4 with iron powder and perform ball milling to obtain product 5.
[0015] C2. Add the product V into 4,4'-dicyclohexylmethane diisocyanate, and stir and mix thoroughly to obtain the component C.
[0016] In some preferred embodiments, the mass ratio of the short-cut halloysite nanotubes to the sodium hexametaphosphate in step A1 is (165-180):1.
[0017] In some preferred embodiments, the alkaline Tween 20 aqueous solution in step A2 has a pH of 8-9 and a mass concentration of 10-20 wt%.
[0018] In some preferred embodiments, the mass ratio of the short-cut halloysite nanotubes to the γ-aminopropyltriethoxysilane and the anhydrous sodium carbonate in step A2 is (30-35):(98-102):1.
[0019] In some preferred embodiments, the mass ratio of the precipitate to the polytetrahydrofuran ether diol in step A2 is (9.5-10):1.
[0020] In some preferred embodiments, the mass ratio of the guanidine carbonate to the ethyl acetoacetate in step B1 is 1:(1.4-1.8).
[0021] In some preferred embodiments, the mass ratio of the product 1 to the hexamethylene diisocyanate in step B2 is 1:(9.8-10.8).
[0022] In some preferred embodiments, the mass ratio of the product 2 to the 2-amino-1,3-propanediol in step B3 is (2-3):1.
[0023] In some preferred embodiments, the mass ratio of the product three to the polymer polyol in step B4 is 1:(9-10).
[0024] In some preferred embodiments, the mass ratio of the anhydrous sodium bicarbonate to the zinc sulfate heptahydrate in step C1 is 1:(1.85-2).
[0025] In some preferred embodiments, the mass ratio of the product four to the iron powder in step C1 is (1.4-1.65):1.
[0026] In some preferred embodiments, the mass ratio of the product V to the 4,4'-dicyclohexylmethane diisocyanate in step C2 is 1:(6-6.8).
[0027] In some preferred embodiments, the composition comprises 30-45 parts of component A, 10-20 parts of component B and 20-35 parts of component C, by weight.
[0028] Another aspect of the present invention is to provide a method for preparing the high-toughness tunnel filling material, comprising the following steps:
[0029] (1) weighing the component A, the component B and the component C in proportion and setting aside;
[0030] (2) The component A is ultrasonically dispersed at room temperature for 1-3 hours, a portion of the component C is added, and the reaction is stirred at 53-55° C. for 1-2.5 hours, cooled to room temperature, the component B is added, and the reaction is ultrasonically dispersed at room temperature for 1-2 hours, and the remaining amount of the component C is added, and the reaction is stirred and dispersed at 300-450 rpm, and the reaction is molded into a mold for 72-120 hours to obtain the product.
[0031] The beneficial effects of the present invention are:
[0032] The present invention provides a high-toughness tunnel filling material. The material adopts a toughening and reinforcing component A containing amino-modified short-cut halloysite nanotubes, a toughening component B with excellent toughening performance, and a reinforcing component C containing iron-doped nano zinc oxide. Through a chemical curing reaction at room temperature, a tunnel filling material with both high toughness and high strength is prepared. Specifically, the present invention effectively combines the toughening component B containing a functional group that can form a dimer through self-complementary quadruple hydrogen bonds and excellent toughening performance, the reinforcing and toughening component A containing amino-modified short-cut halloysite nanotubes containing both soft and hard segment molecular chains, and the reinforcing component C containing rigid nano zinc oxide, to form a unique soft and hard segment microphase separation composite toughening system. In the room temperature curing and molding process, the synergistic reinforcing and toughening capabilities of different components can be effectively exerted, the overall mechanical properties of the material are improved, and the tunnel filling material has good toughness, fatigue resistance and isotropy. DETAILED DESCRIPTION
[0033] The present invention is further described in conjunction with the following examples.
[0034] Example 1
[0035] A high-toughness tunnel filling material, consisting of component A, component B and component C, wherein:
[0036] The preparation method of component A comprises the following steps:
[0037] A0, mechanically crushing the halloysite and screening it with 600 mesh for standby use; placing 40 stainless steel balls with a diameter of 5 mm and 30 stainless steel balls with a diameter of 10 mm in two identical 8L nylon jars, respectively, and then adding 3.5 kg of the screened halloysite, respectively, and then dropping 500 ml of anhydrous ethanol, respectively, and sealing with nylon caps, symmetrically placing the two ball milling jars in a planetary ball mill, and ball milling for 24 hours at a rotation speed of 350 rpm and automatically changing the rotation direction every 30 minutes to obtain short-cut halloysite nanotubes;
[0038] The halloysite powder is commercially available, and its main specifications are: Properties: white powder; Density: 2.4-2.5 g / cm 3 ; Length: <1.1μm; Tube inner diameter: 15-20nm; Tube outer diameter: 40-60nm; Specific surface area: 52.6m 2 / g; Composition: Al2O3: 40.96, SiO2: 58.23, Fe2O3: 0.34, P2O5: 0.14, TiO2: 0.15;
[0039] A1. The short-cut halloysite nanotubes were dispersed in 25 L of water, and the pH was adjusted to 8-9 with a 15% sodium hydroxide aqueous solution. 20 g of sodium hexametaphosphate was added and stirred for 12 h. The mixture was ultrasonicated in a 40 kHz, 400 W ultrasonic cleaning machine for 1 h at room temperature. The mixed system after ultrasonication was centrifuged at 1500 rpm for 15 min. The supernatant was centrifuged at 3500 rpm for 20 min, the supernatant was centrifuged at 6500 rpm for 25 min, the supernatant was centrifuged at 9500 rpm for 30 min, and the precipitate was collected to obtain short-cut halloysite nanotubes with an average length of 350-420 nm for standby use.
[0040] A2, adding 3.3 kg of short-cut halloysite nanotubes obtained in step A1 to a Tween20 aqueous solution with a pH of 8 and a concentration of 15 wt%, ultrasonically dispersing for 6 hours, filtering and separating the precipitate, washing with water, vacuum drying at 78-80°C for 24 hours, and then mixing with 10.6 L of γ-aminopropyltriethoxysilane and 0.1 kg of anhydrous sodium carbonate, stirring and reacting at 82°C for 24 hours, cooling to room temperature after the reaction is completed, centrifuging at 8500 rpm for 20 minutes, collecting the precipitate and washing it with anhydrous ethanol and tetrahydrofuran, respectively, vacuum drying at 35°C for 24 hours, and obtaining 3.1 kg of amino-modified halloysite nanotubes in the form of white powder; adding it to 30 kg of polytetrahydrofuran ether glycol, ultrasonically dispersing it at room temperature for 5 hours, stirring it at 40°C for 4 hours, and cooling it to room temperature to obtain 38.1 kg of the amino-modified toughened and reinforced component A, which is a white liquid mixture containing uniformly dispersed solid particles;
[0041] The Tween 20 is commercially available, and its main specifications are as follows: properties: light yellow viscous liquid; active matter: 98-99%; hydroxyl value (KOHmg / g): 80-108; saponification value (KOHmg / g): 40-50; acid value (KOHmg / g): ≤1.0; HLB value: 16.7; moisture (%): ≤1.0;
[0042] The polytetrahydrofuran ether diol is a commercially available chemically pure product and has been subjected to vacuum dehydration treatment at 130° C. for 5 h;
[0043] The γ-aminopropyltriethoxysilane, anhydrous ethanol, tetrahydrofuran and anhydrous sodium carbonate are all commercially available chemically pure products;
[0044] The preparation method of component B comprises the following steps:
[0045] B1, adding 4.5 kg of guanidine carbonate and 7.2 kg of ethyl acetoacetate to 45 L of anhydrous ethanol, stirring and reacting at 78-80 ° C for 15 hours, cooling to room temperature, separating the precipitate and washing with deionized water, ethanol and acetone, and vacuum drying at 45 ° C for 24 hours to obtain 9.6 kg of product 1 in the form of white powder;
[0046] B2, adding 4.6 kg of the product 1 to 48 kg of hexamethylene diisocyanate, stirring the reaction at 98-100 ° C for 18 hours, cooling to room temperature, adding 50 L of petroleum ether and stirring for 3 hours, separating the precipitate and washing it with petroleum ether, and drying it under vacuum at 48 ° C for 24 hours to obtain 53 kg of product 2;
[0047] B3, 3.5 kg of the product II and 1.6 kg of 2-amino-1,3-propylene glycol were added to 120 L of N,N-dimethylformamide, and the mixture was stirred at 98-100 ° C for 5 hours, and the precipitate was removed. The supernatant was added with a mixed solution of 60 L of ethyl acetate and 60 L of petroleum ether, and the mixture was stirred for 4 hours. After separation of the precipitate and washing with anhydrous acetone, 3.7 kg of product III was obtained after vacuum drying at 55 ° C for 36 hours;
[0048] B4, adding 3.7 kg of the product 3 to 35 kg of polymer polyol, dispersing by ultrasonication at room temperature for 3 h, stirring and mixing at 35 ° C for 3 h, cooling to room temperature, and obtaining 38.1 kg of component B, which is a yellow liquid mixture containing uniformly dispersed solid particles;
[0049] The polymer polyol is a commercially available chemically pure product: functionality: 2; molecular weight: 4050; hydroxyl value: 26.5-29.5; acid value: ≤0.05; water content: ≤0.05; viscosity: 700-1000, and is vacuum dehydrated at 120°C for 8 hours before use;
[0050] The anhydrous ethanol, ethyl acetoacetate, acetone, guanidine carbonate, ethyl acetate, hexamethylene diisocyanate, petroleum ether, N,N-dimethylformamide and 2-amino-1,3-propylene glycol are all commercially available chemically pure products;
[0051] The preparation method of component C comprises the following steps:
[0052] C1. 10 kg of anhydrous sodium bicarbonate and 19.5 kg of zinc sulfate heptahydrate were mixed and milled in a high-energy ball mill for 3 h. The milled product was washed with deionized water, heated to 220° C. in air and kept warm for 3.5 h. After cooling, product 4 was obtained in the form of white powder.
[0053] C2, 4.5 kg of the product 4 was mixed with 3 kg of iron powder, and the mixture was put into a high-energy ball mill for 48 hours to obtain 7.3 kg of product 5, which is an iron-doped zinc oxide nanomaterial with a particle size of 30-50 nm;
[0054] C3, adding 7.3 kg of the product V to 45 kg of 4,4'-dicyclohexylmethane diisocyanate, dispersing by ultrasonication at room temperature for 7 h, stirring and mixing at 60° C. for 6 h, cooling to room temperature, to obtain 52.3 kg of the component C, which is a light yellow liquid mixture containing uniformly dispersed solid particles;
[0055] The 4,4'-dicyclohexylmethane diisocyanate is commercially available, with appearance: colorless liquid; effective ingredient content: 99%; density (25°C, g / ml): 1.066-1.096; refractive index (n20D): 1.497; boiling point: 168°C / 1.5 mmHg.
[0056] The zinc sulfate heptahydrate, pure iron powder and anhydrous sodium bicarbonate are all commercially available chemically pure products;
[0057] The preparation method of the high-toughness tunnel filling material comprises the following steps:
[0058] (1) Weigh the components in proportion, and calculate by mass: 40 parts of component A, 17 parts of component B, and 30 parts of component C, and set aside;
[0059] (2) Component A was ultrasonically dispersed at room temperature for 2.5 hours, 2 / 3 of the mass of component C was added, stirred and reacted at 55° C. for 2 hours, cooled to room temperature, component B was added, ultrasonically dispersed at room temperature for 1.5 hours, the remaining 1 / 3 of component C was added, stirred and dispersed at high speed at 400 rpm for 8 minutes, and molded into a mold at room temperature for 105 hours to obtain the product.
[0060] Example 2
[0061] A high-toughness tunnel filling material, composed of component A, component B and component C, wherein the preparation methods of component A, component B and component C are the same as those in Example 1, and the preparation method of the high-toughness tunnel filling material comprises the following steps:
[0062] (1) Weigh the components in proportion, and calculate by mass: 30 parts of component A, 10 parts of component B, and 20 parts of component C, and set aside;
[0063] (2) Component A was ultrasonically dispersed at room temperature for 1 hour, 2 / 3 of the mass of component C was added, stirred and reacted at 53° C. for 1 hour, cooled to room temperature, component B was added, ultrasonically dispersed at room temperature for 1 hour, the remaining 1 / 3 of component C was added, stirred and dispersed at high speed at 300 rpm for 5 minutes, and molded into a mold at room temperature for 72 hours to obtain the product.
[0064] Example 3
[0065] A high-toughness tunnel filling material, composed of component A, component B and component C, wherein the preparation methods of component A, component B and component C are the same as those in Example 1, and the preparation method of the high-toughness tunnel filling material comprises the following steps:
[0066] (1) Weigh the components in proportion, namely, 45 parts of component A, 20 parts of component B and 35 parts of component C by mass, and set aside;
[0067] (2) Component A was ultrasonically dispersed at room temperature for 3 hours, 2 / 3 of the mass of component C was added, stirred and reacted at 55° C. for 2.5 hours, cooled to room temperature, component B was added, ultrasonically dispersed at room temperature for 2 hours, the remaining 1 / 3 of component C was added, stirred and dispersed at high speed at 450 rpm for 10 minutes, and molded into a mold at room temperature for 120 hours to obtain the product.
[0068] Example 4
[0069] A high-toughness tunnel filling material, composed of component A, component B and component C, wherein the preparation methods of component A, component B and component C are the same as those in Example 1, and the preparation method of the high-toughness tunnel filling material comprises the following steps:
[0070] (1) Weigh the components in proportion, and calculate by mass: 35 parts of component A, 13 parts of component B, and 25 parts of component C, and set aside;
[0071] (2) Component A was ultrasonically dispersed at room temperature for 2 hours, 2 / 3 of the mass of component C was added, stirred and reacted at 54° C. for 1.5 hours, cooled to room temperature, component B was added, ultrasonically dispersed at room temperature for 1.5 hours, the remaining 1 / 3 of component C was added, stirred and dispersed at high speed at 350 rpm for 6 minutes, and molded into a mold at room temperature for 90 hours to obtain the product.
[0072] Experimental example
[0073] The mechanical properties of the high-toughness tunnel filling materials described in Examples 1-4 were tested, and the test results are shown in Table 1.
[0074] (1) Tensile strength and elongation at break
[0075] Test method: Refer to GB 9641-1988 "Test method for tensile properties of rigid foam plastics", use a 5-ton universal testing machine, adopt displacement control, and the loading rate of the testing machine is 5mm / min.
[0076] Specimen size: dumbbell-shaped specimen, specimen thickness is 10mm, width is 40mm, the distance between the two end clamps is 100mm; the gauge length of the middle tensile section is 50mm and the width is 25mm.
[0077] (2) Elastic modulus
[0078] Test method: Referring to GB / T 506-2005 "Test method for strength of cement mortar", the uniaxial compression test was carried out using a 30-ton universal mechanical testing machine. The test adopted displacement control and the loading rate of the testing machine was 0.2mm / min.
[0079] Specimen size: 70.7×70.7×70.7mm.
[0080] (3) Compressive strength and ultimate compressive failure strain
[0081] The test method is the same as that of (2) elastic modulus.
[0082] Specimen size: 70.7×70.7×70.7mm.
[0083] Table 1 Mechanical properties of high toughness tunnel filling materials described in Examples 1-4
[0084] Mechanical performance indicators Example 1 Example 2 Example 3 Example 4 Tensile strength(MPa) 7.1 5.69 9.17 6.86 Elongation at break (%) 73 120 69 64 Elastic modulus (MPa) 11.7 6.3 16 7.5 Compressive strength(MPa) 25.7 12.8 25.9 20.5 Compression failure strain (%) 71.3 61.2 64.5 65.6
[0085] The mechanical property test results show that the high-toughness tunnel filling material provided by the present invention can be molded at room temperature, and its tensile strength is 5.69-9.17MPa, which is higher than that of traditional elastomer rubber (the compressive strength of butyl rubber with a hardness of 70 is 14.7MPa, and the elastic modulus is 2-4MPa), the elongation at break is 64-120%, the elastic modulus is 6.3-16MPa, the compressive strength is 12.8-25.9MPa, and the compression failure strain is 61.2-71.3%; the material can be completely restored after the compressive stress is removed, and is a high-toughness material, which can be used in engineering fields such as tunnel filling and has good application prospects.
[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A high-toughness tunnel filling material, characterized in that: The invention comprises component A, component B and component C, wherein the preparation method of component A comprises the following steps: A1. Disperse short-cut halloysite nanotubes in water, adjust the pH to alkaline, add sodium hexametaphosphate, stir and mix, and then perform ultrasonic treatment. Centrifuge the mixed system after ultrasonication at 1000-2000 rpm for 10-20 min, take the supernatant and centrifuge at 3000-4000 rpm for 15-25 min, take the supernatant and centrifuge at 6000-7000 rpm for 20-30 min, take the supernatant and centrifuge at 9000-10000 rpm for 25-35 min, collect the precipitate and set aside; A2, ultrasonically dispersing the short-cut halloysite nanotubes obtained in step A1 in an alkaline Tween 20 aqueous solution, separating the precipitate, washing with water, drying, mixing with γ-aminopropyltriethoxysilane and anhydrous sodium carbonate, stirring and reacting at 80-85° C. for 22-28 hours, cooling after the reaction, separating the precipitate and washing with anhydrous ethanol and tetrahydrofuran, respectively, vacuum drying, adding to polytetrahydrofuran ether glycol, and ultrasonically dispersing and mixing to obtain the component A; The preparation method of component B comprises the following steps: B1, adding guanidine carbonate and ethyl acetoacetate to anhydrous ethanol, stirring and reacting at 78-80° C. for 12-18 hours, cooling to room temperature, separating the precipitate and washing with deionized water, ethanol and acetone, and drying to obtain product 1; B2, adding the product 1 to hexamethylene diisocyanate, stirring and reacting at 98-100° C. for 16-20 hours, cooling to room temperature, adding petroleum ether, stirring and mixing, separating the precipitate, washing with petroleum ether, and drying to obtain product 2; B3, adding the product II and 2-amino-1,3-propanediol to N,N-dimethylformamide, stirring and reacting at 98-100° C. for 4-7 hours, removing the precipitate, adding a mixed solution of ethyl acetate and petroleum ether to the supernatant, stirring and mixing thoroughly, separating the precipitate and washing it with anhydrous acetone, and drying to obtain the product III; B4, adding the product three to the polymer polyol, and mixing thoroughly to obtain the component B; The preparation method of component C comprises the following steps: C1. Mix anhydrous sodium bicarbonate and zinc sulfate heptahydrate and perform ball milling. Wash the ball milled product with deionized water, heat it to 200-250° C. and keep it for 3-5 hours, and then cool it to obtain product 4. Mix product 4 with iron powder and perform ball milling to obtain product 5. C2. Add the product V into 4,4'-dicyclohexylmethane diisocyanate, and stir and mix thoroughly to obtain the component C.
2. A high-toughness tunnel filling material according to claim 1, characterized in that: In step A2, the mass ratio of the short-cut halloysite nanotubes to the γ-aminopropyltriethoxysilane and the anhydrous sodium carbonate is (30-35):(98-102):1; the mass ratio of the precipitate to the polytetramethylene ether glycol is (9.5-10):
1.
3. The high-toughness tunnel filling material according to claim 1, characterized in that: The mass ratio of the guanidine carbonate to the ethyl acetoacetate in step B1 is 1:(1.4-1.8).
4. The high-toughness tunnel filling material according to claim 1, characterized in that: The mass ratio of the product 1 to the hexamethylene diisocyanate in step B2 is 1:(9.8-10.8).
5. The high-toughness tunnel filling material according to claim 1, characterized in that: The mass ratio of the product 2 to the 2-amino-1,3-propanediol in step B3 is (2-3):
1.
6. The high-toughness tunnel filling material according to claim 1, characterized in that: The mass ratio of the product three to the polymer polyol in step B4 is 1:(9-10).
7. The high-toughness tunnel filling material according to claim 1, characterized in that: In step C1, the mass ratio of the anhydrous sodium bicarbonate to the zinc sulfate heptahydrate is 1:(1.85-2); the mass ratio of the product four to the iron powder is (1.4-1.65):
1.
8. The high-toughness tunnel filling material according to claim 1, characterized in that: The mass ratio of the product five to the 4,4'-dicyclohexylmethane diisocyanate in step C2 is 1:(6-6.8).
9. The high-toughness tunnel filling material according to claim 1, characterized in that: By mass, the composition comprises 30-45 parts of component A, 10-20 parts of component B and 20-35 parts of component C.
10. A method for preparing a high-toughness tunnel filling material according to any one of claims 1 to 9, characterized in that: The following steps are involved: (1) weighing the component A, the component B and the component C in proportion and setting aside; (2) The component A is ultrasonically dispersed at room temperature for 1-3 hours, a portion of the component C is added, and the reaction is stirred at 53-55° C. for 1-2.5 hours, cooled to room temperature, the component B is added, and the reaction is ultrasonically dispersed at room temperature for 1-2 hours, and the remaining amount of the component C is added, and the reaction is stirred and dispersed at 300-450 rpm, and the reaction is molded into a mold for 72-120 hours to obtain the product.